Adult minimal change disease with acute kidney injury: a case report and literature review - P. Daniel Nicholas; Ian Garrahy (Greater Baltimore Medical Center, 2019)
Minimal Change Disease (MCD) is identified via renal biopsy as the etiology of nephrotic syndrome in a minority of adult cases; however, a significant proportion of these occurrences are accompanied by acute kidney injury (AKI). Risk factors for AKI in MCD include increased age, male sex, hypertension, and marked proteinuria and hypoalbuminemia. The etiology of AKI appears to be tubular injury as demonstrated with biomarkers, and although it is usually reversible with steroid therapy, resistance and relapses can occur and may require the use of second-line agents. We present a case of an adult patient with acute onset of biopsy-proven MCD and AKI demonstrating a partial response to corticosteroids and aggressive diuresis and later relapsing and requiring further immunosuppression with tacrolimus. Ultimately, further studies are required to determine the optimal treatment regimen for MCD to ensure remission and avoid relapse.